Effectiveness of Telemedicine Health for Patients with Diabetic Foot Ulcers Care - Muhammad Anis Taslim; Zaky Mubarak; Siti Nafisah (NHM PRESS, 2022)
Introduction: Diabetic foot ulcers one of the complications that often occur in patients with Diabetes Mellitus. Telemedicine is an established means of using evolving telecommunication technology to obtain and disseminate medical data and services. This systematic review aims to ensure the effectiveness of telemedicine for the management of diabetic foot ulcer care. Method: We used “telemedicine” to restrict our search to “healing” and “diabetic foot” and used “diabetic foot ulcers”, keywords, and abstract connected by the Boolean operator “AND”. Search articles using the PICOT framework in the international database; EBSCO, Science Direct, Scopus, ProQuest, limited to the last five years, 2017 to 2021, obtained 15 articles the inclusion criteria studies focused on telemedicine in a patient with diabetic foot ulcer care. The articles were included Randomized Control Trial, quasi-experiment. Other design studies were included in exclusion criteria. was performed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) rules. Results: The outcome shows that telemedicine accessible a few innovations accessible that adequacy esteem in the observing, anticipation, and treat diabetic foot ulcers. Ends: Telemedicine skin thermography, photograph imaging, and mobile phone online innovation show comparative gives great outcomes in recuperating viability for patients with diabetic foot ulcers care.